LANGUAGE MARGINALIZATION AND (POSSIBLE) LANGUAGE RACIALIZATION IN THE INDONESIAN HIGHER-EDUCATION ENGLISH PEDAGOGY - Purnama, Arry (CALL, 2025)
This study describes the subtle practice of language marginalization in the Indonesian higher-education English pedagogy. Employing an autoethnographic method to scrutinize my personal narratives concerning assumptions, biases, and internalized ideologies, I formulated two research questions to guide the inquiry: (1) How does language marginalization take form in the teacher-student interactions and teachers’ perception toward students in the context of Indonesian higher-education English pedagogy? (2) How do these practices of language marginalization relate to language racism in the context of Indonesian higher-education English pedagogy? Through this study, I argue that language marginalization could occur tacitly in any English higher-education subject where students had to showcase their English production, such as speaking and writing courses. This is when their English productions are complained and appropriated due to the internalized monolingual ideology. Language marginalization could also ensue in any classes whether or not teachers demand students to demonstrate their English productive skills. In this case, the phenomenon is bolstered by the teachers’ attitudes and assumptions on students based on students’ physical phenotypes and language production. I also demonstrate how language marginalization relates to language racism in Indonesia’s higher-education settings, in a way that both occur simultaneously and the former fuels the latter. Finally, I suggest some recommendations for Indonesian English teacher for more productive, just pedagogical practices.